(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article dedicates the complexities Helmut Dalov faced in translating Boburnoma, written by Zahiriddin Muhammad Babur, into German. The work’s national characteristics and rich linguistic features present substantial challenges in translation. We analyze Dalov’s methods in dealing with culturally embedded concepts, linguistic structures, and multilingual elements within Boburnoma, focusing on the impact of his approach on the text’s readability and fidelity to the original. The findings highlight the strategies Dalov employed to maintain the spirit of Babur’s work while adapting it for a German-speaking audience, illustrating the nuanced balance required in translating culturally significant literature